COMPARATIVE ANALYSIS OF THE KEY ENGLISH AND RUSSIAN LANGUAGE TERMS IN STUDIES OF INTEREST GROUP POLITICS - I. I. Pisarev (Vestnik MGIMO-Universiteta)
This research article investigates the Russian equivalents of the key terms of the English language interest group politics research vocabulary in relation to the issues that their application is causing in research publications. The study is based on the terminological and statistical analyses of the following terms of the interest group politics: lobbying, advocacy, and interest groups and the Russian equivalents that derive from them. The article offers a detailed analysis and comparison of the essential properties of these Russian equivalents to identify the most suiting of them with an ultimate goal of harmonization of the Russian research vocabulary of the interest group politics.Terminological analysis of the study has revealed 22 closest Russian equivalents of the three English terms, including 5 Russian equivalents of the term lobbying, 9 Russian equivalents of the term advocacy, and 8 Russian equivalents of the term interest groups. Statistical analysis of the application of these 22 selected Russian equivalents studied in timeframe between 1992 and 2016 is based on the investigation of the research publication databases of the www.cyberleninka.ru website. The purpose of this analysis was to identify the most frequently used Russian equivalents of the English terms under study selected from a pool of options revealed during terminological analysis.Based on the terminological and statistical analyses of the pool of the Russian equivalents of the three key terms of the English language interest group politics research vocabulary, the author identifies the most highly recommended ones of them for application in the Russian language research publications.